The Stellar Mass–Black Hole Mass Relation at z ∼ 2 down to Determined by HETDEX - Yechi Zhang; Masami Ouchi; Karl Gebhardt; Chenxu Liu; Yuichi Harikane; Erin Mentuch Cooper; Dustin Davis; Daniel J. Farrow; Eric Gawiser; Gary J. Hill; Wolfram Kollatschny; Yoshiaki Ono; et al. (The Astrophysical Journal, 2023)
We investigate the stellar mass–black hole mass ( ${{ \mathcal M }}_{* }--{{ \mathcal M }}_{BH}$ ) relation with type 1 active galactic nuclei (AGNs) down to ${{ \mathcal M }}_{BH}={10}^{7\,}{M}_{\odot }$ , corresponding to a ≃ −21 absolute magnitude in rest-frame ultraviolet, at z = 2–2.5. Exploiting the deep and large-area spectroscopic survey of the Hobby–Eberly Telescope Dark Energy Experiment (HETDEX), we identify 66 type 1 AGNs with ${{ \mathcal M }}_{BH}$ ranging from 10 ^7 –10 ^10 M _⊙ that are measured with single-epoch virial method using C iv emission lines detected in the HETDEX spectra. ${{ \mathcal M }}_{* }$ of the host galaxies are estimated from optical to near-infrared photometric data taken with Spitzer, the Wide-field Infrared Survey Explorer, and ground-based 4–8 m class telescopes by CIGALE spectral energy distribution (SED) fitting. We further assess the validity of SED fitting in two cases by host-nuclear decomposition performed through surface brightness profile fitting on spatially resolved host galaxies with the James Webb Space Telescope/NIRCam CEERS data. We obtain the ${{ \mathcal M }}_{* }--{{ \mathcal M }}_{BH}$ relation covering the unexplored low-mass ranges of ${{ \mathcal M }}_{BH}\,\sim \,{10}^{7}--{10}^{8}\,M_{\odot }$ , and conduct forward modeling to fully account for the selection biases and observational uncertainties. The intrinsic ${{ \mathcal M }}_{* }--{{ \mathcal M }}_{BH}$ relation at z ∼ 2 has a moderate positive offset of 0.52 ± 0.14 dex from the local relation, suggestive of more efficient black hole growth at higher redshift even in the low-mass regime of ${{ \mathcal M }}_{BH}\,\sim \,{10}^{7}--{10}^{8}\,M_{\odot }$ . Our ${{ \mathcal M }}_{* }--{{ \mathcal M }}_{BH}$ relation is inconsistent with the ${{ \mathcal M }}_{BH}$ suppression at the low- ${{ \mathcal M }}_{* }$ regime predicted by recent hydrodynamic simulations at a 98% confidence level, suggesting that feedback in the low-mass systems may be weaker than those produced in hydrodynamic simulations.